2020
DOI: 10.1016/j.ssaho.2020.100054
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus at the end of the world: Antarctica matters

Abstract: The potential impact of coronavirus in Antarctica through tourism and scientific research as well as the Antarctic Treaty System is reviewed over three time periods. In the short term, to April 2021, Antarctic tourism and field-based research will be severely reduced. The impact on Antarctic governance means that few, if any, international meetings will take place thereby leaving discussions on issues, such as fishing quotas, uncertain. Looking to the medium term, to April 2024, polar tourism is unlikely to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…SIOS-KC coordinates the services provided by SIOS for the international research community and ensures sustainability and maintenance of the network. The services offered include: (1) integration of the distributed research infrastructure and data to optimise the observing system, (2) access to the research infrastructure (SIOS ACCESS programme), (3) data management including storing and curating of scientific data (ground-based, airborne and spaceborne), (4) tools and support for scientists to make use of the extensive Earth observation (EO) and remote sensing (RS) resources available, (5) coordination of logistical services, (6) training and education programmes, and (7) information and outreach. EO and RS activities are important parts of the observing system as certain key data can be measured with satellite-based observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIOS-KC coordinates the services provided by SIOS for the international research community and ensures sustainability and maintenance of the network. The services offered include: (1) integration of the distributed research infrastructure and data to optimise the observing system, (2) access to the research infrastructure (SIOS ACCESS programme), (3) data management including storing and curating of scientific data (ground-based, airborne and spaceborne), (4) tools and support for scientists to make use of the extensive Earth observation (EO) and remote sensing (RS) resources available, (5) coordination of logistical services, (6) training and education programmes, and (7) information and outreach. EO and RS activities are important parts of the observing system as certain key data can be measured with satellite-based observations.…”
Section: Introductionmentioning
confidence: 99%
“…Several transnational access projects in the Arctic supported by EU-INTERACT (https://eu-interact.org/) have been affected during the field season in 2020 with around 120 scientists had to cancel their field campaigns. Frame and Hemmings [5] reviewed the potential impact of COVID-19 in Antarctica through tourism and scientific research over three (short-term, mid-term, and long-term) time periods. According to these authors, Antarctic tourism and field-based research will be severely reduced in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…During the process of undertaking the research described (2019)(2020), the COVID-19 pandemic has made a profound impact globally including on Antarctica. The medium and long-term implications of this in general, and specifically on Antarctic tourism, are very unclear and are likely to remain so for some time (Frame & Hemmings, 2020). The paper was written on the premise of a projected expansion of Antarctic tourism though the authors anticipate that this will change considerably.…”
Section: Introductionmentioning
confidence: 99%
“…[42,[60][61][62] Set the priority of tourism research Other crises cannot be ignored, such as Antarctic scientific expeditions and oil spills on cruise ships. [63,64] In this theme, scholars emphasized the importance of tourism research and education for the management of people's values, community goals, and government goals during the COVID-19 crisis, thus calling on scholars to play their role. Universities have always played a leading role in society.…”
mentioning
confidence: 99%
“…Due to the global economic recession caused by COVID-19 and the diversion of research attention, some research on other crises that are occurring has been forced to stop or slow down. For example, Frame [63] reviewed the potential impact of COVID-19 on Antarctica through tourism and scientific research and the Antarctic Treaty System, and found that in the short term to April 2021, Antarctic tourism and field research will be greatly reduced. Likewise, Junior [64] found that due to COVID-19 and the economic crisis, efforts to understand and resolve the oil spill crisis off the coast of Brazil had to be stopped (or slowed down), leaving the ecosystem and society with no answers to determine the cause of the problem and understand how to mitigate its impact on the community and the environment.…”
mentioning
confidence: 99%